Analisis Praktikum Organisasi Kehidupan Dan Permasalahannya di SMP se-KecamatanTeluk Betung Utara - Marista Nia; Berti Yolida; Arwin Achmad (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
The aims of this research were to analyze the implementation of laboratory practice and its problems on living organism materials of junior high schools in Teluk Betung Utara. The samples were selected by purposive sampling. Data collection technique used questionnaire, interview, and observation, its analyzed using Miles and Huberman model. Research results showed that the laboratory practice on living organism materials was categorized as very good category, observation result of laboratory practice was good, and students laboratory practice worksheet was quite good. Problems appeared in the implementation of laboratory practice on living organism materials were limited number microscopes; laboratory practice activities was not conducive yet; lack of preparation before conducting the laboratory practice, and the students laboratory practice worksheet not directing the students yet in order to formulate a hypothesis. Based on the results of this study, it can be concluded that the implementation of laboratory practice and its problems on living organism materials in Teluk Betung Utara was categorized as very good although there was some problems existed in the laboratory practice implementation.Penelitian ini bertujuan menganalisis pelaksanaan praktikum materi organisasi kehidupan dan permasalahannya di SMP se-Kecamatan Teluk Betung Utara. Sampel dipilih secara purposive sampling. Teknik pengambilan data menggunakan angket, wawancara, dan observasi, yang dianalisis dengan model Miles dan Huberman. Hasil penelitian pelaksanaan praktikum berkriteria sangat baik, observasi tahapan pelaksanaan praktikum berkriteria baik, LKS-praktikum/LKPD-praktikum berkriteria cukup baik. Permasalahan dalam pelaksanaan praktikum yaitu keterbatasan jumlah mikroskop; kegiatan praktikum yang masih kurang kondusif; persiapan sebelum melaksanakan praktikum masih kurang, serta penyusunan LKS-praktikum/ LKPD-praktikum belum mengarahkan siswa untuk merumuskan hipotesis. Berdasarkan hasil penelitian dapat disimpulkan bahwa pelaksanaan praktikum materi organisasi kehidupan se-Kecamatan Teluk Betung Utara berkriteria sangat baik walaupun terdapat permasalahan dalam pelaksanaan praktikum.Kata kunci: organisasi kehidupan, pelaksanaan praktikum, permasalahan praktikum